(untitled) (Al-Qamar, 2021)
This article provides the fundamental aspects of healthcare in context of its sociological discipline. It includes the systemic collection and evaluation of integral parts of biomedical and sociological concepts of healthcare and their amalgamation in making a therapeutic plan to provide the fastest recovery to remedy seekers. The importance of assessment regarding the strengths, weaknesses, opportunities and threats associated with personnel, environmental and sociological issues has also been discussed, along with the advantages of its implementation in current healthcare system to attain maximum beneficial effects. This study also provides an insight into the pragmatic insights of Prophetic assessments in which the Holy Prophet PBUH provided remedies to the seekers after evaluating their physical as well as sociological factors, particularly the ones associated with their presented complaints. By finding the importance of sociological concept of health in accordance with Sunnah, this research peeps through the cognitive and behavioral ways of modern therapeutics. It concludes that besides treating the diseased part of patient’s side, the team of healthcare professionals must pay heed towards the mind, spirit and emotions of the patients.